An investigation into the influence of autoignition chemistry and charge cooling under 'Beyond RON' operating conditions on the improved knock resistance of ethanol over iso-octane - Bock, Bradley (Department of Mechanical Engineering, 2014)
The growing interest in alcohol fuels has led to the finding that benefits in terms of efficiency and power compared to traditional petrols can be gained due to the improved knock resistance of alcohols. This improved knock resistance has been widely credited to the differences in autoignition chemistry and charge cooling caused by the alcohols’ high latent heat of vapourisation. This interest initiated a research project to further understand the influence exerted by the autoignition chemistry and high latent heat of vapourisation in the alcohols’ higher knock resistance. Ethanol and iso-octane were chosen as the representative fuels for alcohols and traditional petrols respectively. The study was conducted through a modelling exercise that made use of experimental data to calibrate subsections of the model and validate the overall model performance. The experimental investigation made use of a boosted 0.45 ` single cylinder Port Fuel Injected (PFI) engine with a specially designed manifold. The manifold allowed for upstream injection of the fuel and recording of the evaporative cooling that occurred along the length. The engine was run under a number of operating conditions and the knock limited spark advance was determined to capture a measure of the knock resistance of the respective fuels at each operating point. The modelling study consisted of a steady state one-dimensional evaporative model to predict the charge cooling caused by the fuels in the inlet manifold under the various conditions that the fuels were exposed to. A two-zone zero dimensional combustion model with an empirical knock model was implemented to study the influences of differences in inlet air cooling and autoignition chemistries on the knock resistance. The modelling study showed that the autoignition chemistry plays the largest role in determining the magnitude of ethanol’s advantage over iso-octane. The size of this advantage is dependant on the operating temperatures experienced, with cooler temperature increasing ethanol’s advantage. This is due to iso-octane’s cool flame phenomenon, which widens the gap in knock resistance between the fuels at low temperatures due to its greater influence under these conditions. The evaporation modelling showed that there is only a small difference in cooling between the fuels under the conditions they experienced in the test engine. However literature points to direct injection as a technology that may offer the opportunity to take further advantage of the cooling potential of ethanol.